Short-term amendment of biosolid on agricultural soil: effects on C and N mineralization and microbial activity - Medina-Herrera, Miriam del Rocío; Negrete-Rodríguez, María de la Luz Xochilt; Prieto-Rojas, Manuel Alberto; Bedolla-Rivera, Héctor Iván; Barajas, Eloy Conde (Acta Universitaria, 2022)
Adding biosolids to agricultural soils can improve its quality through increased storage of C and N. A study to analyze the short-term impact of the addition of biosolids on the release of nutrients and the microbial activity in agricultural soil was carried out. The microbial biomass C (MB-C), urease activity (UA), and mineralization of N and C at different application rates of biosolids were evaluated (0 mg, 100mg and 200 mg of N-NH4+ kg-1). In addition, a biosolid-only treatment was tested. It was observed an increase in C and N mineralization, NH3 volatilization, and MB-C content, according to the application rate of biosolids. In biosolid treatments, UA increased 100% on average in the first seven days of incubation. These results suggest that the nutrient content in the soil is improved and microbial activity is positively stimulated.
Keywords: Array; Array; Array; Array